Antimicrobial susceptibility testing of Mycobacteroides (Mycobacterium) abscessus complex, Mycolicibacterium (Mycobacterium) fortuitum, and Mycobacteroides (Mycobacterium) chelonae. Issue 2 (February 2019) - Aono, Akio; Morimoto, Kozo; Chikamatsu, Kinuyo; Yamada, Hiroyuki; Igarashi, Yuriko; Murase, Yoshiro; Takaki, Akiko; Mitarai, Satoshi
Abstract: The drug susceptibility of rapidly growing mycobacteria (RGM) varies among isolates. Treatment strategies similarly differ depending on the isolate, and for some, no clear strategy has been identified. This complicates clinical management of RGM. Following Clinical and Laboratory Standards Institute standard M24-A2, we assessed the susceptibility of 140 RGM isolates to 14 different antimicrobial drugs by measuring their minimal inhibitory concentrations (MICs). We also investigated the correlation of clarithromycin (CAM) MICs with the erm (41) and rrl gene mutations in the Mycobacteroides ( Mycobacterium ) abscessus complex, the rrl mutation in Mycobacteroides ( Mycobacterium ) chelonae, and the erm (39) mutation in Mycolicibacterium ( Mycobacterium ) fortuitum to determine the contribution of these mutations to CAM susceptibility. The five species and subspecies examined included 48 M. abscessus subsp. abscessus isolates (34.3%), 35 (25.0%) being M. abscessus subsp. massiliense, and two (1.4%) being M. abscessus subsp. bolletii. The M. abscessus complex accounted for 85 isolates (60.7%) in total, whereas 43 isolates (30.7%) were M. fortuitum, and 12 (8.6%) were M. chelonae . Our results demonstrated species-specific susceptibility to antimicrobials. In most cases, susceptibility to CAM could be predicted based on genetic pattern, but since one isolate did not fit that pattern, MIC values needed to be measured. Some isolates also exhibited rates of resistance to other drugs that differed from those previously reported in other locations, indicating that accurate identification of the bacterial isolate and use of the correct method for determining MIC are both important for the diagnosis of RGM.